Lived experience and impact of oral phosphodiesterase-5 inhibitors among patients with type 2 diabetes mellitus complicated by erectile dysfunction: A qualitative study - Ramali, Khairul Nazli; Draman, Nani; Zainuddin, Aida Maziha; Muhamad, Rosediani; Ismail, Shaiful Bahari (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
This study explored the experiences of men with Type 2 Diabetes Mellitus (T2DM) who also experienced erectile dysfunction (ED) and delayed seeking medical treatment. Using a phenomenological approach, in-depth interviews were conducted with 15 male patients, aged 18 and above, who had been using phosphodiesterase-5 (PDE5) inhibitors for at least three months. Thematic analysis of the interviews, framed by sexual script theory, identified three key themes. Patients reported feelings of sexual distress, a perceived loss of manhood, and inadequacy as husbands, which negatively affected their wives and relationships. Many initially believed that alternative therapies could cure ED, delaying their pursuit of conventional medical treatment. However, after complementary treatments failed, they recognized the benefits of PDE5 inhibitors. These medications significantly helped patients regain sexual strength, self-esteem, and satisfaction in their relationships. This study underscores the profound impact ED has on the sexual well-being of men with T2DM and highlights the importance of PDE5 inhibitors in improving sexual function and restoring intimacy within couples. It also emphasizes the need for early intervention and education on the effectiveness of medical treatments for ED.